Предмет: Алгебра,
автор: kirpichnikov
решите уравнение 3х/ 2 - (2х - 3) / 4 =3
Ответы
Автор ответа:
0
3х/ 2 - (2х - 3) / 4 =3
6х - (2х - 3) = 12
6х - 2х + 3 = 12
4х = 9
х = 2,25
или
х= 2 1/4 ( две целых одна четвертая)
6х - (2х - 3) = 12
6х - 2х + 3 = 12
4х = 9
х = 2,25
или
х= 2 1/4 ( две целых одна четвертая)
Похожие вопросы
Предмет: Биология,
автор: Аноним
Предмет: Алгебра,
автор: BasNas
Предмет: Русский язык,
автор: ershovmaxim366
Предмет: Физика,
автор: nickeya
Предмет: Алгебра,
автор: Tomi31